Svetozar Marković: “Serbia in the East” or “Greater Serbia” - Šutović, Milojica (Sociološki pregled, 2026)
Svetozar Marković, through his interrelated ideas, was the first to create a systematized body of knowledge about Serbian society, to provide its explanation, and to foresee its future development. In doing so, he fulfilled, in the modern sense, the most significant criteria of the definition of the sociological theory and authored a comprehensive socio-political study “Serbia in the East”, in which he criticized and contested the program of “Greater Serbia”. Both will be the subject of the analysis, with the aim of demonstrating their theoretical, practical-political, and national significance. This will be approached from the perspective of the critical social theory, the theory of nationalism, and the systems theory of society. At the same time, consideration will be given to his ideological standpoint as the first Serbian socialist and the first Serbian “radical sociologist” with sociological imagination.
Keywords: Svetozar Marković (1846–1875); socialist; radical sociology; Serbia in the East; Greater Serbia